Fabrication of novel direct Z-scheme + isotype heterojunction photocatalyst g-C3N4/TiO2 with peroxymonosulfate (PMS) activation synergy and 2D/0D structure. Issue 23 (1st November 2022) - Zhang, Bowen; Wu, Mingkun; Chen, Zhengjun; Dong, Lihui; Li, Bin; Tao, Lin; Wang, Haonan; Li, Danyang
Abstract : A novel strategy for fabricating C3 N4 /TiO2 Z-scheme heterojunctions based on C3 N4 isotype heterojunctions is presented. This scheme exploits the structural plasticity of C3 N4 to achieve a breakthrough in activity without adding new materials. Abstract : Using a simple ultrasonic dispersion technique, a 2D/0D structured g-C3 N4 /TiO2 isotype + Z-scheme heterojunction photocatalyst with PMS activation synergy was produced for the breakdown of organic pollutants under solar light irradiation. XRD, FTIR spectroscopy, SEM-EDS, HRTEM, XPS, and ESR, amongst others, were used to evaluate the samples' structure, morphology, optical, and electronic features. As demonstrated by the structure and morphology, the TiO2 nanoparticles were dispersed uniformly in a thin g-C3 N4 nanolayer. Rhodamine B (Rh-B) was broken down under simulated sunlight to measure the photocatalytic activity of the synthesized samples. The outstanding activity of the g-C3 N4 /TiO2 photocatalysts was attributed to the creation of an isotype + Z-scheme that aided the separation of photogenerated carriers and the maintenance of excellent electronic redox capacity. This study offers an excellent method for constructing a Z-scheme photocatalytic system supported by isotype heterojunction, providing a potential blueprint for the development of high-performance photocatalysts suitable for pollution control.